Airbnb – exploring triple bottom line impacts on community. Issue 2 (13th March 2020) - Caldicott, Rodney W.; von der Heidt, Tania; Scherrer, Pascal; Muschter, Sabine; Canosa, Antonia
Abstract : Purpose: This paper aims to purposely place community and its stakeholders at the forefront of an investigation of positive and negative social, economic and environmental impacts of the sharing economy in the specific context of Airbnb by drawing upon the triple bottom line (TBL) framework of sustainability. Design/methodology/approach: A qualitative enquiry through a "scoping approach" with the search of relevant electronic databases identified a range of conceptual and empirical studies in the period from 2008 to 2018 informing a profile focussed on the triple bottom line impacts. Findings: The criteria limited search yielded 23 focal articles, which investigated or discussed Airbnb impacts on local communities. Analysis of these articles informed a three-pillar tabulation of positive and negative impacts, which are presented against four key stakeholder groupings. Research limitations/implications: The study is exploratory, and further research, especially confirmatory research, is recommended. Practical implications: The study's value extends to praxis. Guided by findings, real-time planning and policy-making are already underway within the authors' community. Additionally, an extension project, as requested by the community, is now investigating direct traditional accommodation provider impacts. Social implications: Understanding of the social issues concerning Airbnb and indeed, the wider sharing economy, is broadened through identified need for further social impact research. Originality/value: To the best of authors' knowledge, this is one of the first studies to apply a "scoping approach" to holistically illuminate the positive and negative impacts of Airbnb at the micro-level in each of the three domains of sustainability. The research methodology is shown to be effective, with positive community impact, and will easily adapt to other destinations grappling with policy decisions.